Rainfall Prediction In Bengkulu City Fuzzy Logic-Based - Yessi Mardiana; Toibah Umi Kalsum; Yoli Andi Rozzi (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
The purpose of this study is to predict the rainfall in the city of Bengkulu using fuzzy logic . The boundary problem in this research is a fuzzy method used is Fuzzy Method Sugeno , testing was conducted using the software Matlab version 2013a , the data used in this study is the rainfall data from October to December 2015 were taken from the Meteorology , Climatology and Geophysics , the Center for Meteorology , Climatology and Geophysics ( BMKG ) Bengkulu. Of a series of studies conducted with reference to the design of the block diagram of the results obtained in the form of cuara on the day or the future (tomorrow) with Sugeno mentode this is to conduct experiments for 7 days with accuracy levels of over 60%. From 7 days forecasting error occurred as much as 2 days